Defect detection mechanisms with induction and conduction thermography: current flow and defect-specific warming. Issue 2 (2nd April 2020) - Vrana, Johannes; Goldammer, Matthias
ABSTRACT: Active thermography with electromagnetic excitation, is a reliable non-destructive evaluation method with a wide range of applications. It allows detecting inhomogeneities, like cracks, at or close to the surface of conductive components fast and reliable utilizing infrared imaging. Electric current can be used in two ways for thermography: In induction thermography a current is coupled to the component by passing an AC current through a coil which is close to the inspected component, while in conduction thermography the current is coupled directly into the component. Over the past years the basics of electromagnetic excitation, including the influence of the material of the component to be tested and the necessary post-processing algorithms have been studied. In this paper parameter studies on a comprehensive variety of defect models and their detection mechanisms are presented. Starting with delamination type defects, both within a component and between a coating and the component. Continuing with crack type defects open to the surface, like the well-known slot and notch type cracks, contact-point and 'area of reduced conductivity' type cracks. For those types' parameters like depth, width, length, inductor position, rotation, inclination, and conductivity are discussed. The paper concludes with sub-surface cracks and cracks hidden under non-conductive coatings.